HARMONIZING INDONESIA'S GEOGRAPHICAL INDICATION PROTECTION WITH EU LEGAL FRAMEWORK THROUGH REGULATORY REFORM - Zuliarti, Wa Ode; Yuningsih, Deity; Deschika Gaby Justicia; Isnayanti; Faisal, Fitriah (JIPRO: Journal of Intellectual Property, 2026)
Indonesia’s GI protection under Law Number 20 of 2016 integrates with trademarks, creating ownership ambiguity that disadvantages small producers and limits EU recognition. Employing a doctrinal legal method combined with a comparative approach, this study systematically analyses statutory texts, regulatory documents, and academic literature from both jurisdictions. Comparing with EU’s sui generis system, this study identifies three challenges: conceptual conflation of collective/private rights, administrative overlap, and governance allowing holder control. Despite 209 registered GIs across 34 provinces, only four have EU recognition, revealing systemic barriers. The EU model treats GIs as community entitlements open to all qualifying producers with representative governance. The study recommends targeted reforms: clarifying GI rights as non-transferable collective entitlements, functionally separating GI from trademark administration within Directorate General of Intellectual Property (DGIP), and establishing conflict rules for geographical names. These reforms would enhance rural development and international market access.